PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Kasus pada Perusahaan Manufaktur - Kabupaten Serang) - Rahmiyanti, Sev (JURNAL RISET AKUNTANSI TIRTAYASA, 2017)
This study examined the effect of working satisfaction, organizational commitment and compensation on accounting employee performance . This study took a manufacturing company located in Serang as the object of research. The number of samples in this study were 83 respondents. Data were analyzed by using SEM (Structural Equation Model) by SmartPLS program (Partial Least Square) version 1.0. The results of this study states that compensation effects job satisfaction. Job satisfaction influences employee performance. Compensation effects employee performance. Compensation effects organizational commitment. Organizational commitment influences employee performance. Manufacturing companies are expected to be used as a tool to evaluate and improve performance. Further research is expected to add external variable factors (incentives, organizational culture, etc.) and add more respondents. The next research is also expected to develop further research of various other business entities, such as the banking, hotel, service, commercial or state-owned.Keywords: Working Satisfaction, Organizational Commitment, Compensation, Accounting Employee Performance.